Development of a Comic-Based Mathematics E-Handout on Trigonometry Material to Improve Learning Outcomes of 10th Grade Students of SMA Negeri 5 Surakarta in the 2024/2025 Academic Year - Nesthi Wahyuningsih; Ira Kurniawati (Universitas Muhammadiyah Semarang, 2025)
This research focuses on the development of comic-based e-handouts on Trigonometry material for class X students of SMA Negeri 5 Surakarta for the 2024/2025 academic year. The main objectives of this research are to find out how the e-handout development process, the validity of the e-handou t developed, the practicality of the e-handout developed, and measure the effectiveness in improving student learning outcomes. This research uses the ADDIE development model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The subjects of this study were 33 students of class X-E6 SMA Negeri 5 Surakarta in the 2024/2025 academic year. Data were collected through interviews, documentation, questionnaires, and tests. The results showed that: (1) the comic-based e-handout development process uses the ADDIE development model and digital platforms in the form of Canva, Heyzine, Padlet, Quizizz, and Google Forms; (2) the validity of the e-handout gets an average score of 0.9027 from the validation of material and media experts which is included in the very high validity category; (3) teacher responses have an average score with a percentage of 79.33%, included in the practical category; (4) student responses have an average score with a percentage of 83.5%, also included in the very practical category; (5) the average increase in N-Gain is 0.75 or 75.18%, classified as a high increase with sufficient effectiveness. Based on these results, it is concluded that the comic-based e-handout developed is valid, practical, and effective in improving student learning outcomes, and is suitable for use to deepen understanding of Trigonometry concepts for grade X high school students.